EFFECT OF ISLAMIC FINANCIAL LITERACY, TRUST IN THE INTEREST IN USING DIGITAL WALLETS - Astrid Aulia Farizki; Hastuti Olivia; Widia Astuty (Journal of Islamic, Social, Economics and Development, 2023)
The lack of Islamic financial literacy in generation Z in sharia transactions means that there are still many generation Z using non-sharia digital wallet applications. This study aims to see how the role of generations plays a role in transactions in accordance with sharia and to see the effect of Islamic financial literacy, trust in the interest in using digital wallet applications in generation Z. There were 160 respondents to this study who were 4th semester students of the Department of Islamic Accounting who had received courses sharia accounting. This study used a quantitative method with the SmartPLS 3.0 test tool. The results of this study are that Islamic financial literacy has no effect on interest and trust has an effect on students' interest in using digital wallet applications. The lack of Islamic financial literacy means that many generations of Z still use non-sharia digital wallet applications.